A Study of Disaster and Firm’s Revival - Dube, Partha (Journal of Finance, Business and Management Studies, 2026)
This article examines the problem of a manager who plans at struggle the disaster of conflicts of war and epidemic while reducing the social costs. An interesting point may be observed in our model. If we move forward to slow policies then it may regulate the fast effective spread rate of the disease which obeys a dispersive randomness. We present a comprehensive theoretical analysis demonstrating the formation of the most favourable policy. In all our tests the latter is demonstrated by three different stages: the disaster is first freely affect the units of a firm and damaged it vigorously and then the manager of the firm tries to put up a fight against the disaster and finally a regeneration policy is adopted to revive the damaged units. Stochastic process indicates the premature position of the disease in its first stage with the positions of the boost growing rate of the disaster which is controlled after a long time.